YB1 regulates miR‐205/200b‐ZEB1 axis by inhibiting microRNA maturation in hepatocellular carcinoma. Issue 7 (10th June 2021) - Liu, Xiumei; Chen, Di; Chen, Huan; Wang, Wen; Liu, Yu; Wang, Yawei; Duan, Chao; Ning, Zhen; Guo, Xin; Otkur, Wuxiyar; Liu, Jing; Qi, Huan; et al.
Abstract: Background: Y‐box binding protein 1 (YB1 or YBX1) plays a critical role in tumorigenesis and cancer progression. However, whether YB1 affects malignant transformation by modulating non‐coding RNAs remains largely unknown. This study aimed to investigate the relationship between YB1 and microRNAs and reveal the underlying mechanism by which YB1 impacts on tumor malignancy via miRNAs‐mediated regulatory network. Methods: The biological functions of YB1 in hepatocellular carcinoma (HCC) cells were investigated by cell proliferation, wound healing, and transwell invasion assays. The miRNAs dysregulated by YB1 were screened by microarray analysis in HCC cell lines. The regulation of YB1 on miR‐205 and miR‐200b was determined by quantitative real‐time PCR, dual‐luciferase reporter assay, RNA immunoprecipitation, and pull‐down assay. The relationships of YB1, DGCR8, Dicer, TUT4, and TUT1 were identified by pull‐down and coimmunoprecipitation experiments. The cellular co‐localization of YB1, DGCR8, and Dicer were detected by immunofluorescent staining. The in vivo effect of YB1 on tumor metastasis was determined by injecting MHCC97H cells transduced with YB1 shRNA or shControl via the tail vein in nude BALB/c mice. The expression levels of epithelial to mesenchymal transition markers were detected by immunoblotting and immunohistochemistry assays. Results: YB1 promoted HCC cell migration and tumor metastasis by regulating miR‐205/200b‒ ZEB1 axis partially in a Snail‐independent manner. YB1 suppressed miR‐205 and miR‐200b maturation by interacting with the microprocessors DGCR8 and Dicer as well as TUT4 and TUT1 via the conserved cold shock domain. Subsequently, the downregulation of miR‐205 and miR‐200b enhanced ZEB1 expression, thus leading to increased cell migration and invasion. Furthermore, statistical analyses on gene expression data from HCC and normal liver tissues showed that YB1 expression was positively associated with ZEB1 expression and remarkably correlated with clinical prognosis. Conclusion: This study reveals a previously undescribed mechanism by which YB1 promotes cancer progression by regulating the miR‐205/200b‒ ZEB1 axis in HCC cells. Furthermore, these results highlight that YB1 may play biological functions via miRNAs‐mediated gene regulation, and it can serve as a potential therapeutic target in human cancers. Abstract : YB1 regulates miR‐205/200b‐ ZEB1 axis by inhibiting microRNA maturation.